2021
DOI: 10.3390/beverages7040074
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Sensory Fingerprint of Swedish Beer Market through Text and Data Mining and Multivariate Strategies

Abstract: The continuous increase of online data with consumers’ and experts’ reviews and preferences is a potential tool for sensory characterization. The present work aims to overview the Swedish beer market and understand the sensory fingerprint of Swedish beers based on text data extracted from the Swedish alcohol retail monopoly (Systembolaget) website. Different multivariate strategies such as heatmaps, correspondence analysis and hierarchical cluster analysis were used to understand the sensory space of the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…These beers were characterized with more tropical and fruity aromas (i.e., passion fruit or mango). Conversely, beers containing AM hops were characterized by the absence of these tropical fruits, rather showing notes of “coffee,” “cocoa/chocolate” or “spicy.” These results are in agreement with the recent findings from Garrido‐Bañuelos, Buica, et al (2021) (Garrido‐Bañuelos, de Barros Alves, & Mihnea, 2021), where the sensory space of specific hops was investigated through text data. Nonetheless, a recent study has shown how the taster's beer styles preference can influence the perceptual maps and aromatic description of hop varieties (Hopfer et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These beers were characterized with more tropical and fruity aromas (i.e., passion fruit or mango). Conversely, beers containing AM hops were characterized by the absence of these tropical fruits, rather showing notes of “coffee,” “cocoa/chocolate” or “spicy.” These results are in agreement with the recent findings from Garrido‐Bañuelos, Buica, et al (2021) (Garrido‐Bañuelos, de Barros Alves, & Mihnea, 2021), where the sensory space of specific hops was investigated through text data. Nonetheless, a recent study has shown how the taster's beer styles preference can influence the perceptual maps and aromatic description of hop varieties (Hopfer et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…" These results are in agreement with the recent findings fromGarrido-Bañuelos, Buica, et al (2021) (Garrido-Bañuelos, de Barros Alves, & Mihnea, 2021, where the sensory space of specific hops was investigated through text data. Nonetheless, a recent study has shown how the taster's beer styles preference can influence the perceptual maps and aromatic description of hop varieties(Hopfer et al, 2021).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Various enzymatic reactions and microbial activities modify and improve the flavor properties of food and make it more palatable. Aroma is an organoleptic characteristic that is perceived by the olfactory organ over the hypopharynx (Garrido-Bañuelos et al, 2021). However, the term "flavor" involves all characteristics of the food components held in the mouth.…”
mentioning
confidence: 99%